Role of visual social networking, hypersensitive narcissism, and anxiety sensitivity in online compulsive buying - Phil Reed (Telematics and Informatics Reports, 2023)
The impact of hypersensitive narcissism and anxiety sensitivity on online compulsive buying were examined. These transdiagnostic personality factors have not previously received attention in virtual, as opposed to real-world, contexts, and the study explored their interaction with the use of visual and textual social media platforms for online buying. The present study sampled 440 participants (264 female; 174 male), aged 18 – 37 years. Participants completed an online survey comprising: Online Edwards Compulsive Buying Scale Revised, Hypersensitive Narcissism Scale, and the Anxiety Sensitivity Index-3. Visual social networking usage was a risk factor for online compulsive buying, and there were significant positive relationships between both hypersensitive narcissism, and anxiety sensitivity, with online compulsive buying. Anxiety sensitivity mediated the relationship between hypersensitive narcissism and compulsive online buying when the dominate form of social media use was textual, but not when it was visual.